2011
DOI: 10.19030/jabr.v10i1.5958
|View full text |Cite
|
Sign up to set email alerts
|

The Directional Influence Of Music Backgrounds In Television Advertising

Abstract: <span>Advertisers frequently incorporate music backgrounds in television commercials as a means of improving ad effectiveness. This paper examines the relationship of alternative music backgrounds on brand attitude formation. Brand attitudes were more favorable when emotive cues deviated from neutral presentations in circumstances of high involvement and when emotive cues were positive in situations of low involvement. Implications for advertising practice as well as suggestions for future research are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Music appears to be an important stimulus in an advertisement. As the previous work shows (Abolhasani et al , 2017; Bozman et al , 1994), consumers are more likely to respond positively to advertisements involving liked music. In addition, the prior research on advertising information processing often suggests that consumer purchase intention commonly represents the ultimate positive response (Frias et al , 2008).…”
Section: Theory and Hypothesesmentioning
confidence: 60%
See 1 more Smart Citation
“…Music appears to be an important stimulus in an advertisement. As the previous work shows (Abolhasani et al , 2017; Bozman et al , 1994), consumers are more likely to respond positively to advertisements involving liked music. In addition, the prior research on advertising information processing often suggests that consumer purchase intention commonly represents the ultimate positive response (Frias et al , 2008).…”
Section: Theory and Hypothesesmentioning
confidence: 60%
“…In line with this theoretical perspective, we assume an indirect effect whereby music liking can stimulate the development of consumers’ favourable attitudes towards the firm’s brand, which in turn affects their purchase intention. Prior studies partially support this assumption and highlight the association between music liking and positive brand attitudes (Bozman et al , 1994; Mittal, 2015), as well as the connection between positive brand attitudes and consumer purchase intention (Davtyan et al , 2020; Hartmann and Apaolaza-Ibáñez, 2012). Yet, adequate empirical tests of this assumption remain lacking.…”
Section: Introductionmentioning
confidence: 87%
“…Although this study provided no support for the argument that music with stronger positive feelings is more effective, it found partial support for the hypothesis that advertisements with familiar music are more effective than those with unfamiliar music in the context of brand recall and recognition. Bozman et al (1994) examined the relationships between various types of background music (liked music, disliked music and neutral music), and brand attitudes under high-and low-involvement conditions. They found that, in the low-involvement condition, brand attitudes were more favourable for positive emotive cues (i.e.…”
Section: Familiarity Of Background Music and Consumers' Responsesmentioning
confidence: 99%
“…For association congruity, music associated with an unpleasant experience lowered brand evaluation (Blair & Shimp, 1992). In valence congruity, musical taste reinforces the attitude toward the brand (Mitchell, 1988), musical dislike decreases the attitude toward the brand (Simpkins & Smith, 1974), and musical taste increases the attitude toward the brand when involvement with advertising is low (Bozman et al, 1994;Park & Young, 1986). The results on semantic congruity, in turn, suggested that the high congruence between the ad, the lyrics, and the message reinforced the attitude towards the brand with low and increased involvement with the advertising (MacInnis & Park, 1991).…”
Section: Congruencymentioning
confidence: 99%